SEIZE TRADITION SIX SISAMPEK ON HOLIDAY IN DISTRICT KUANTAN REGENCY KUANTAN SINGINGI - Desmawati '; Bedriati Ibrahim Bedriati Ibrahim; Marwoto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Indonesia is one country that is very rich with ethnic and cultural variety, diversity of culture in the territory of Indonesia is something that ought to be proud of by the community itself. Tradition into parts of the past that is maintained until now. In Kuantan District Regency know a tradition called tradition seize Sisampek, this tradition has been handed down by the community Kuantan Regency and still survive. Regency Kuantan community mostly Muslim, in the month of Shawwal is full of grace and victory, this month there are also rituals that have added value for Muslims, especially in Kuantan District Regency after the first Eid usually people do fasting six days in Shawwal until the seventh day. Then on the eighth day they perform Hari Raya Six. In today's feast Six Kuantan Regency communities celebrate the tradition of seizing Sisampek celebration. The research goal is to determine the history of the origins of the tradition of the feast Sisampek seize six, to know how to seize the implementation process Sisampek tradition on the feast of six, the values contained in this tradition. Factors that cause began to decrease enthusiastic people to this tradition. This study used a qualitative approach to data collection techniques used were interviews, observation, documentation and literature. This research was conducted in the District of Kuantan Hilir Regency Kuantan Singingi. The results showed that this tradition is divided into three stages of preparation, filling stage and stage Sisampek seizure. This tradition has the values of solidarity, social values, religious values, and ethical values. Factors causing the community began to decrease due to the tradition of social relations are increasingly stretched, community economic factors and the drive that has begun is not running anymore.Keywords: Tradition, Sisampek, The Feast of six